Hip Labral Reconstruction With a Polyurethane Scaffold: Restoration of Femoroacetabular Contact Biomechanics. Issue 9 (9th September 2022) - Capurro, Bruno; Reina, Francisco; Carrera, Anna; Monllau, Joan Carles; Marqués-López, Fernando; Marín-Peña, Oliver; Torres-Eguía, Raúl; Tey-Pons, Marc
Background: Many advances have been made in hip labral repair and reconstruction and in the restoration of the suction seal. Purpose/Hypothesis: The purpose of this study was to evaluate the biomechanical effects of segmental labral reconstruction with a synthetic polyurethane scaffold (PS) in comparison with segmental labrectomy. Our hypothesis was that reconstruction with a icroporous polyurethane implant would normalize joint kinetics of the hip and restore the suction seal. Study Design: Controlled laboratory study. Methods: We used 10 hips from 5 fresh-frozen pelvises with an intact acetabular labrum without osteoarthritis. Using an intra-articular pressure measurement system, the contact area, contact pressure, and peak force were assessed for the following conditions: intact labrum, partial anterosuperior labrectomy, and PS reconstruction. For each condition, all specimens were analyzed in 4 positions (90° of flexion, 90° of flexion and internal rotation, 90° of flexion and external rotation, and 20° of extension) and underwent a labral seal test. The relative change from the intact condition was determined for all conditions and positions. Results: Compared with the intact labrum, labrectomy resulted in a significant decrease in the contact area ( P < .001) and a significant increase in the peak force ( P < .001) and contact pressure ( P < .001) across all positions. Compared with labrectomy, PS reconstruction resulted in a significant increase in the contact area ( P < .001) and a significant decrease in the contact pressure ( P ≤ .02) and peak force ( P < .001) across all positions. Compared with the intact labrum, PS reconstruction restored the contact area and peak force to normal values in all positions ( P > .05), whereas the contact pressure was significantly decreased compared with labrectomy ( P < .05) but did not return to normal values. The labral seal was lost in all specimens after labrectomy but was restored in 80% of the specimens after PS reconstruction. Conclusion: Femoroacetabular contact biomechanics significantly worsened after partial labrectomy; reconstruction using a PS restored the contact area and peak force to the intact state and improved the contact pressure increases seen after partial labrectomy. The contact area and peak force were normalized, and the labral seal was re-established in most cases. Clinical Relevance: This study provides biomechanical evidence for the use of a scaffold for labral reconstruction.